2018
DOI: 10.1007/s40263-018-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid-Based Therapies and Brain Development: Potential Harmful Effect of Early Modulation of the Endocannabinoid System

Abstract: The endocannabinoid retrograde signaling pathway is widely expressed in the central nervous system, where it plays major roles in regulating synaptic plasticity (excitatory and inhibitory) through long-term potentiation and long-term depression. The endocannabinoid system (ECS) components-cannabinoid receptors, endocannabinoids and synthesis/degradation enzymes-are expressed and are functional from early developmental stages and throughout adolescent cortical development, regulating progenitor cell fate, neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 96 publications
(127 reference statements)
0
31
0
Order By: Relevance
“…This endocannabinoid system is functional from the early developmental stages and throughout adolescent cortical development. Schonhofen et al [27] also observed that the endocannabinoid system, among others, regulates progenitor cell fate, neural differentiation, migration, and survival. Given this, it is not surprising that the endocannabinoid system may be particularly vulnerable to excessive cannabinoid exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This endocannabinoid system is functional from the early developmental stages and throughout adolescent cortical development. Schonhofen et al [27] also observed that the endocannabinoid system, among others, regulates progenitor cell fate, neural differentiation, migration, and survival. Given this, it is not surprising that the endocannabinoid system may be particularly vulnerable to excessive cannabinoid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Such vulnerability appears to be related to the greater sensitivity of the endocannabinoid system [26]. More specifically, Schonhofen et al [27], in their overview, noted the importance of the endocannabinoid retrograde signaling pathway in regulating both excitatory and inhibitory synaptic plasticity via long-term potentiation and long-term depression. Cannabinoid receptors, endocannabinoids, and synthesis or degradation enzymes form the endocannabinoid system (ECS).…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term effects on cognition is one major concern with cannabinoid treatment (21). Longer observational periods and studies with a more detailed neurocognitive test protocol are needed.…”
Section: Discussionmentioning
confidence: 99%
“…) and endogenous arachidonic acid (AA)‐derived mediators, are synthesized from membrane phospholipids (Alswat ) and are directly involved in synaptic plasticity and cortical development (Schonhofen et al. ). The therapeutic potential of cannabinoids in seizures is well described (Perucca ; Rosenberg et al.…”
Section: Introductionmentioning
confidence: 99%